Improvement of DART Algorithm Teletsunami Detection Response through Lengthening the Prediction Time - Sampurno, Tri; Ayuningtyas, Fara; Riski, Miranti Jatnika; Shaleha, Siti; Santosa, Agung; Pragesjvara, Vitria; Gunawan, Made (2023 International Conference on Computer, Control, Informatics and its Applications (IC3INA), 2023)
The DART (Deep-ocean Assessment and Reporting of Tsunamis) tsunami detection algorithm, developed by the National Oceanic and Atmospheric Administration (NOAA) in 1997, is an automatic and real-time tsunami detection method used in various Tsunami Early Warning Systems, including the Indonesia Tsunami Early Warning System (InaTEWS). The DART algorithm's performance was evaluated using data from several tsunami cases in the Pacific Ocean from 2006 to 2022, and it was discovered that teletsunamis were not always correctly detected by the DART algorithm. There have been situations where the DART algorithm successfully detected tsunamis but required an extended period (more than 2 hours from the arrival of the tsunami), and cases where the DART algorithm was unable to detect the arrival of a tsunami signal properly. The proposed solution in this paper is to increase the prediction time of the DART algorithm up to 7.75 minutes, which has been empirically proven to reduce the detection time of teletsunamis by at least 10 minutes and up to 2.64 hours and can identify previously undetected teletsunamis.